Perbandingan Mutu Kerupuk Teripang (Holuthuria Scabra) Olahan Dengan Kerupuk Komersial - Nelfa Yulianti; Dwi Apriliani AGS (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
In Indonesia, sea cucumbers are widely used as food is from the type of sea cucumber (Holothuria scabra). Sea cucumbers are often processed into dried sea cucumbers and crackers. therefore the researchers made a comparison between the two samples of processed sea cucumber crackers and commercial sea cucumber crackers to determine their quality. Furthermore, to determine differences in the content of the protein content, fat content, ash content, and water content, and hedonic test of crackers cucumbers. The research method is experimental laboratories. The results of testing the protein content of processed sea cucumber crackers by 4.46%, while in commercial sea cucumber crackers by 0.56%, fat content in processed sea cucumber crackers by 0.45%, and in commercial sea cucumber crackers by 0.95%, ash content in processed sea cucumber crackers by 0.01%, and in commercial sea cucumber crackers by 0.51%, and the content of water content in processed sea cucumber crackers was 6.15% and in commercial sea cucumber crackers was 8.94%. The quality of processed sea cucumber crackers and commercial sea cucumber crackers in this study both of the crackers have good quality. The result of hedonic test of processed sea cucumber crackers is 7.44 μ ≥ 8.18 so it is suitable for consumption. In commercial sea cucumber crackers it is 7.56 ≥ μ ≥ 8.26 and is suitable for consumption.